2012
DOI: 10.1371/journal.pone.0045148
|View full text |Cite
|
Sign up to set email alerts
|

Two Goose-Type Lysozymes in Mytilus galloprovincialis: Possible Function Diversification and Adaptive Evolution

Abstract: Two goose-type lysozymes (designated as MGgLYZ1 and MGgLYZ2) were identified from the mussel Mytilus galloprovincialis. MGgLYZ1 mRNA was widely expressed in the examined tissues and responded sensitively to bacterial challenge in hemocytes, while MGgLYZ2 mRNA was predominately expressed and performed its functions in hepatopancreas. However, immunolocalization analysis showed that both these lysozymes were expressed in all examined tissues with the exception of adductor muscle. Recombinant MGgLYZ1 and MGgLYZ2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
30
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 56 publications
4
30
0
Order By: Relevance
“…rVpDef was expressed in Escherichia coli Origami (DE3) (Novagen) as a C-terminal His6-tagged fusion protein using the pET-30a(+) system (Novagen). Expression, purification and refolding of rVpDef were performed according to the methods described previously (Wang et al, 2012). In the present study, the rVpDef was expressed as inclusion bodies and purified by HisTrap Chelating Columns under denatured conditions.…”
Section: Recombinant Expression and Mass Spectrometric Analysis Of Rvmentioning
confidence: 99%
“…rVpDef was expressed in Escherichia coli Origami (DE3) (Novagen) as a C-terminal His6-tagged fusion protein using the pET-30a(+) system (Novagen). Expression, purification and refolding of rVpDef were performed according to the methods described previously (Wang et al, 2012). In the present study, the rVpDef was expressed as inclusion bodies and purified by HisTrap Chelating Columns under denatured conditions.…”
Section: Recombinant Expression and Mass Spectrometric Analysis Of Rvmentioning
confidence: 99%
“…These restricted distribution patterns in birds and mammals contrasted with the broad expression patterns of g-type lysozymes in fish and invertebrate species. G-type lysozymes have been detected in the spleen, kidneys, gills, skin, heart, intestines and blood of Japanese flounder, orange-spotted grouper, large yellow croaker, Atlantic cod and grass carp (Hikima et al, 2001;Savan et al, 2003;Yin et al, 2003;Zheng et al, 2007), as well as in the gills, mantle, hepatopancreas, hemocytes and muscles in Mytilus galloprovincialis (Wang et al, 2012). Real-Time analysis has shown that C. intestinalis g-type lysozymes are upregulated in the pharynx after LPS challenge, in particular, CiLys-g1, CiLys-g2 and CiLys-g3 gene expression were significantly boosted at 24e72 h, while CiLys-g4 gene expression was significantly boosted at 1 h and 2e4 h and decreased at 8e48 h, supporting a defensive role for CiLys-g lysozymes.…”
Section: Discussionmentioning
confidence: 99%
“…For transcript polymorphism detection, two specific primers (P5 and P6, Table 1) designed in the 5 0 UTR and 3 0 UTR were employed to clone the full coding sequence of Rpdefs. The PCR profile and subsequent sequencing were conducted as described previously [33,34]. A total of 126 positive Rpdef clones were bi-directionally sequenced respectively.…”
Section: Total Rna Extraction and Sequence Amplificationmentioning
confidence: 99%
“…Quantitative real-time PCR (qRT-PCR) was carried out in an ABI 7500 Real-time Detection System by using the SYBR ExScript qPCR Kit (Takara, Japan) as described previously [33]. The PCR amplification was carried out in a total volume of 50 mL, containing 25 mL of 2 Â SYBR Green PCR Master Mix, 20 mL of the diluted cDNA, 1 mL of each of primers (10 mmol/L), and 3 mL of DEPC-treated water.…”
Section: Quantitative Real-time Pcr (Qrt-pcr) Assaymentioning
confidence: 99%
See 1 more Smart Citation